Failure behavior of aerial bomb lifting lug under variable amplitude loading: Failure analysis and life prediction. (February 2021) - Wang, Bowen; Xie, Liyang; Song, Jiaxin; He, Xuehong; Luo, Weifeng; Zhao, Bingfeng; Mu, Tong
Highlights: Variable amplitude loading fatigue test and failure analysis of several lifting lug structures were carried out. Oxide inclusion defect induced lifting lug structural failure mode is verified. The proposed method overcomes the shortcomings of traditional fatigue cumulative damage method. The proposed fatigue life prediction method of structure with initial defect is acceptable. Abstract: The lifting lug is one of the most important structures of aerial bomb, which mainly bears the variable amplitude cyclic loading during the working process. In this paper, the failure analysis of several lifting lugs which failed in fatigue test was carried out. Firstly, through the mechanical analysis, fatigue cumulative damage analysis and fracture surface analysis of the lifting lug structure, it was determined that the fracture failure was not caused by the issue of structural design, but by the Al2 O3 inclusion defect in the casting process. Next, the crack source defect was equivalent to the initial crack, and the fatigue full-life was predicted by the method of fatigue crack growth (FCG). The FCG process was divided into two stages: small crack growth stage and long crack growth stage for life prediction respectively. Finally, the validity of this method was verified by comparing with the experimental results, and it was suggested to adopt advanced lifting lug casting and detection technology to prevent similar faults.